2017
DOI: 10.1371/journal.pone.0170476
|View full text |Cite
|
Sign up to set email alerts
|

Retinal vessel density from optical coherence tomography angiography to differentiate early glaucoma, pre-perimetric glaucoma and normal eyes

Abstract: PurposeTo evaluate optic nerve vascular density using swept source optical coherence tomography angiography (OCTA) in patients with early primary open angle glaucoma (POAG), pre-perimetric glaucoma and normal eyes.MethodsThis is a prospective, observational study including 56 eyes in total and divided into 3 groups; 20 eyes with mild POAG, 20 pre-perimetric glaucoma eyes, and 16 age-matched normal eyes as controls. The optic disc region was imaged by a 1050-nm-wavelength swept-source OCT system (DRI OCT Triton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
131
1
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 147 publications
(147 citation statements)
references
References 23 publications
11
131
1
4
Order By: Relevance
“…Significantly lower OCTA parameters (vessel density, blood flow index, and flow index) were found in glaucoma eyes in comparison with normal eyes in the peripapillary area [6, 16-50], the optic disc [19, 23, 25, 32, 36, 51-60] and the whole image macular area [16, 21, 32, 34, 36-38, 61-64]. In all of those areas, the diagnostic abilities increased with increasing severity of glaucoma [32, 34, 52].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Significantly lower OCTA parameters (vessel density, blood flow index, and flow index) were found in glaucoma eyes in comparison with normal eyes in the peripapillary area [6, 16-50], the optic disc [19, 23, 25, 32, 36, 51-60] and the whole image macular area [16, 21, 32, 34, 36-38, 61-64]. In all of those areas, the diagnostic abilities increased with increasing severity of glaucoma [32, 34, 52].…”
Section: Resultsmentioning
confidence: 99%
“…The area under the curve (AUC) for the best discriminating OCTA parameter (vessel density and blood flow index) ranged between 0.75 and 1.00, while for the OCT parameter (RNFL) the values ranged between 0.76 and 0.97 [17, 19, 20, 22, 23, 25, 27, 31, 32, 34, 36, 37, 41, 49]. Most studies found an AUC above 0.850 both for the OCTA parameters [17, 20, 22, 23, 25, 31, 32, 37, 41] and for the RNFL [19, 20, 22, 25, 31, 34, 37, 49].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations